Representations of forced displacement in Colombian fiction cinema: years 2003 to 2011 - Uribe Montes, Jhon Alexander (Escribanía, 2018)
The following exhibition of results is the product of a research project that asks about the way in which the arts rewrite and interpret Colombian history. Specifically, how the Colombian fiction cinema between the years 2003 to 2011 gave account of those multiple realities product of the war. Today, with a peace process signed with the FARC guerrillas and the maximum challenge of an implementation that guarantees real peace, it is pertinent to examine history, build memory processes and draw attention to the strategies used to reveal these realities.